STUDI EKSPERIMENTAL PENGARUH GGBFS DAN SUPERPLASTICIZER TERHADAP KUAT TEKAN DAN MODULUS ELASTISITAS BETON - Susilowati, Anni; Pratikto, Pratikto; Hakim, Haudiah; Raden Bagus Anggietantyo Akiranda (Politeknik Negeri Jakarta, 2025)
The use of alternative materials in concrete mixtures is an important effort to improve concrete performance while reducing dependence on cement. This study aims to investigate the effect of adding Ground Granulated Blast Furnace Slag (GGBFS) as a partial substitute for cement on the properties of concrete, both in fresh and hardened conditions, using a constant dosage of type F superplasticizer at 1% of the cement weight. The GGBFS replacement levels used in this study were 0%, 20%, 30%, and 40%. The tests conducted included slump, unit weight, initial setting time, compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity. The results showed that the use of GGBFS significantly affected compressive strength and splitting tensile strength, with optimum results achieved at the 20% replacement level. In contrast, other properties such as flexural strength and unit weight were not significantly influenced. Therefore, GGBFS can be considered an effective supplementary material in concrete mixtures when used at an appropriate dosage.